Test-retest reliability and sensitivity of kinematic and kinetic metrics measured from horizontal deceleration ability tests with different sprinting distances - Chen, Z.; Lyu, M.; Yin, M.; Deng, S.; Bishop, C.; Harper, D.; Dai, B.; Li, Y. (Journal of Human Kinetics, 2025)
This study aimed to (1) assess the test-retest reliability and sensitivity of kinematic and kinetic metrics from 5-m, 10-m, and 20-m horizontal deceleration ability (HDA) tests; (2) explore the relationships of those metrics from HDA5m, HDA10m and HDA20m tests. Eighteen college athletes completed one familiarization session and two test sessions separated by 48 hours. Test sessions consisted of three 5-m, 10-m, and two 20-m maximal sprints, along with HDA tests conducted at the same sprinting distances. The deceleration-related metrics measured from HDA5m, HDA10m and HDA20m tests showed good-to-excellent overall reliability (ICC > 0.75, CV < 5.81%) and were efficiently sensitive in detecting moderate changes in deceleration performance (SEM < SWC0.5), except for the DTS and TTS of the HDA20m test (ICC: 0.44-0.57, CV: 5.15-6.37%, SEM > SWC0.5). DTS and TTS of the HDA5m test showed non-significant and small to moderate relationships with the HDA10m and HDA20m tests, while all kinetic metrics displayed significant and large to very large correlations among three tests. This suggests that short-distance HDA tests are reliable and sensitive for assessing deceleration performance, and further research is needed to explore the biomechanical and physiological factors influencing this unique ability.